Bioprospekksi Ekstrak Bawang Putih (Allium sativum) Terhadap Infeksi Edwardsiella tarda Pada Ginjal Ikan Lele (Clarias gariepinus): Literature Review - Luckita Budiarti Utami Putri (Journal of Biotropical Research and Nature Technology, 2023)
Catfish (Clarias batrachus) is a freshwater fish that is cultivated commercially by Indonesian people. Catfish is the most widely cultivated fish by the community because it has various advantages such as fast growth rates, high adaptability to the environment such as stocking with high density per unit area of ponds and being able to live in aquatic environments that lack oxygen and has a good taste and high value. high nutrition. However, the presence of Edwardsiella tarda bacteria greatly affects the survival of catfish (Clarias gariepinus) because this bacteria attacks fish. This is a crucial problem because catfish have high economic value and are widely consumed and cultivated. One way that can be done to overcome this problem is by utilizing natural ingredients, namely garlic which is a natural plant that contains antibacterial properties. Garlic is one of the natural plants that contain active ingredients of sulfur compounds such as aliin, allicin, disulfide, trisulfide. This research method uses several articles related to the effect of soaking garlic extract (Allium Sativum) on the histology of catfish kidneys infected with Edwardsiella tarda bacteria and compares the differences between normal catfish kidneys and kidneys infected with Edwardsiella tarda bacteria and proves the content of garlic on catfish kidneys ( Clarias gariepinus) infected with bacteria (Edwardiella tarda)